Q. 26

# Prove that: <span

Proof:

Identities used:

Therefore,

tan 15° = tan (45° - 30°)

On rationalising:

{ (a – b)(a + b) = a2 – b2}

On rationalising

{ (a – b)(a + b) = a2 – b2}

Let 2θ = 15°

We know,

Formula used:

{ (a + b)2 = a2 + b2 + 2ab}

cot θ < 0 as θ is in 1st quadrant.

So,

{ (a + b)2 = a2 + b2 + 2ab}

{ cot θ = tan(90° - θ)}

Hence Proved

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses
RELATED QUESTIONS :

If a cos 2x + b sRD Sharma - Mathematics

If a cos 2x + b sRD Sharma - Mathematics

If a cos 2x + b sRD Sharma - Mathematics

Prove that:
</
RD Sharma - Mathematics

If <RD Sharma - Mathematics

Prove that:
</
RD Sharma - Mathematics

If <RD Sharma - Mathematics

If sec (x + α) + RD Sharma - Mathematics

Prove that:
</
RD Sharma - Mathematics

0 ≤ x ≤ π aRD Sharma - Mathematics